Educational inequalities in cardiovascular mortality in Spanish regions (2016-2021) - Enrique Pérez-Miguel; Sergi Trias-Llimós (Gaceta Sanitaria)
Objective: Cardiovascular diseases (CVD) are the leading cause of death in low-mortality countries, but subpopulation level differences exist. This study assesses educational inequalities in CVD mortality by sex in Spanish regions (2016-2021). Method: Age-standardised mortality rates by sex, region and education were estimated using individual-level mortality data from individuals aged ≥35 years residing in Spain provided by the Spanish National Statistics Institute. The Relative and the Slope Indexes of Inequality (RII and SII) were estimated to assess educational inequalities. Results: For the whole Spain, RII was 1.79 (IC95%: 1.42-2.26) for women and 1.59 (IC95%: 1.33-1.91) for men, with differences across regions. The greatest inequalities were found in the Balearic and Canary Islands, and the lowest in La Rioja. Conclusions: Continued efforts monitoring and tackling cardiovascular morbidity and its determinants are needed at the national and regional level to further contribute to reducing cardiovascular mortality levels and inequalities therein. Resumen: Objetivo: Las enfermedades cardiovasculares (ECV) son la principal causa de muerte en los países de baja mortalidad, aunque presentan desigualdades entre subpoblaciones. Este estudio evalúa desigualdades educativas en mortalidad por ECV según el sexo en las regiones españolas (2016-2021). Método: Se estimaron tasas de mortalidad estandarizadas por edad, sexo, región y nivel educativo utilizando datos individuales de mortalidad de individuos ≥35 años residentes en España, proporcionados por el Instituto Nacional de Estadística. Se estimaron los índices de desigualdad relativa y de pendiente (RII y SII) para evaluar las desigualdades educativas. Resultados: Para toda España, el RII fue de 1,79 (IC95%: 1,42-2,26) para las mujeres y de 1,59 (IC95%: 1,33-1,91) para los varones, observándose diferencias entre regiones. Las mayores desigualdades se encontraron en las Islas Baleares y Canarias, y las menores en La Rioja. Conclusiones: Es necesario continuar con los esfuerzos de seguimiento y abordaje de la morbilidad cardiovascular y sus determinantes en los ámbitos nacional y regional para seguir contribuyendo a reducir los niveles de mortalidad por causa cardiovascular y sus desigualdades.